Meningkatkan Kemampuan Siswa Kelas IX B SMP Negeri 8 Muaro Jambi dalam Menentukan Iklim Matahari pada Pembelajaran Unsur Geografis di Kawasan Asia Tenggara dengan Menggunakan Media Gambar Globe - Akhmad Saiful (Universitas Batanghari Jambi, 2019)
There are still many students who do not know how to determine the climate of a country based on its astronomical location. For this reason, the author tries to try to overcome this problem by conducting a Classroom Action research at Muaro Jambi State Middle 8 where the author is on duty. As for the formulation of the problem is whether using globe picture media can improve the ability of class IX B students of Muaro Jambi Middle School 8 in determining the sun's climate in learning geographical elements in the Southeast Asian region? This study aims to improve the ability of class IX B students of Muaro Jambi Middle School 8 in determining the climate of the sun's climate. This research was conducted in three cycles. Each cycle, students are taught how to determine the climate using a globe. The subject matter set for research is the geographical element in the Southeast Asia region. Before doing research, students' ability to determine climate based on their astronomical location obtained 80.77% of students unable to determine the climate. After doing the research, in the first cycle, which was held in two meetings, 61.54% of students were able to determine the climate. Then in the second cycle, the results of 76.92% of students were able to determine the climate and in the third cycle the results were 88.46% of students able to determine the climate of a country. There was a significant increase in students' abilities. Thus the use of globe image media can be used as an alternative to overcome students' difficulties in determining the climate.